Positive effects of auditory cue in locomotor pattern of people with Parkinson's disease (off and on medication) - Rinaldi, Natalia Madalena; Pereira, Marcelo Pinto [UNESP]; Formaggio, Priscila Matias [UNESP]; Morais, Luana Carolina [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Escola de Educação Física e Esporte da Universidade de São Paulo, 2014)
Gait disorders are identified in people with Parkinson’s disease. The aim of this study was to investigate the effect of auditory cues and medication on kinematic, kinetic and EMG parameters, during different gait phases of people with PD and healthy elderly. Thirty subjects distributed in two groups (Group 1, PD patients off and on medication; Group 2, healthy elderly) participated in this study and were instructed to walk in two experimental conditions: non-cued and cued. Therefore, kinematic, kinetic and electromyography analyses were utilized to investigate the locomotor pattern. Changes in locomotor pattern (greater muscular activity) with auditory cue were observed for PD patients. Regarding the medication, locomotor parameter improvement was observed after levodopa intake in association with the auditory cue. These results confirm the hypothesis about the external cues therapy that could be used as a complement to drug therapy to achieve improvement in the locomotor pattern of PD patients.

Mudanças na marcha são identificadas em pacientes com doença de Parkinson (DP). O objetivo deste estudo foi investigar o efeito da dica auditiva e do medicamento nos parâmetros cinemáticas, cinéticos e eletromiograficos durante diferentes fases da marcha em pacientes com DP e idosos sadios. 30 indivíduos distribuídos em dois grupos (Grupo 1, pacientes com DP; Grupo 2, idosos sadios) participaram deste estudo e foram instruídos a realizarem duas tarefas experimentais: marcha com e sem dica auditiva. Análise cinemática, cinética e eletromiográficas foram utilizadas para investigar o padrão locomotor. Mudanças no padrão locomotor (maior ativação muscular) foram observadas para os pacientes com DP. Em relação à medicação, melhoras no padrão locomotor foram observadas após a ingestão da levodopa em associação com a dica auditiva. Estes resultados confirmam a hipótese sobre a terapia com dicas externas, que pode ser utilizada como um complemento à terapia medicamentosa para melhorar o padrão locomotor de pacientes com DP.
Efeito positivo da dica auditiva no padrão locomotor de pacientes com doença de Parkinson
Keywords: Locomoção; Levodopa; Biomecânica; Dica externa; Envelhecimento; Walking; Levodopa; Biomechanics; External cue; Aging